Inhaled medications and inhalation chambers for childhood asthma. Spanish network of working groups on asthma in pediatrics (REGAP) - Juan Carlos Juliá Benito; Laura Moreno-Galarraga; Esther Bragado Alcaraz; María Teresa Asensi Monzó; Cristina Ortega Casanueva; Luis Moral; Carmen Rosa Rodríguez Fernández-Oliva; José Sanz Ortega; Laura Valdesoiro Navarrete (Elsevier, 2024)
Asthma, the most prevalent chronic disease in pediatric age, continues to pose challenges in its management and treatment. National and international guidelines emphasize the importance of therapeutic education (TE) to achieve disease control. TE involves imparting knowledge and skills to the patient and their family, enhancing medication adherence, rectifying errors in inhalation technique, and tailoring treatment based on individual patient characteristics.It is essential for TE to be progressive, gradual, and personalized, spanning all levels of care. Training healthcare professionals in TE is crucial, particularly for pediatricians, who must also be aware of the extensive variability of available meds and inhalers and their respective age-specific indications.Addressing this need, the REGAP Group extensively reviewed inhalers currently available in Spain for pediatric asthma treatment. The review encompassed different inhalation systems and inhaled drugs used for pediatric asthma treatment. This review will be updated annually, providing information on medications, devices, inhalation chambers, indications, and financiation. The REGAP Group hopes that these tables will be a valuable help for pediatricians in their daily clinical practice and serve as an effective TE tool. Resumen: El asma, la enfermedad crónica más prevalente en la edad pediátrica, continúa planteando desafíos en su manejo y tratamiento.1 Guías nacionales e internacionales destacan la importancia de la educación terapéutica (ET) para lograr el control de esta enfermedad.2,3 Esta educación implica la transmisión de conocimientos y habilidades al paciente y su familia, mejorando la adherencia a la medicación, corrigiendo errores en la técnica de inhalación y ajustando el tratamiento según las características individuales de cada paciente.4,5Es esencial que la ET sea progresiva, gradual e individualizada, y que esté presente en todos los niveles asistenciales. La formación en ET de profesionales sanitarios es crucial, especialmente para los pediatras, quienes además deben conocer la extensa variabilidad de medicamentos e inhaladores disponibles y sus indicaciones para cada edad.6Para abordar esta necesidad, el Grupo REGAP ha revisado exhaustivamente los inhaladores actualmente disponibles en España para el tratamiento del asma en la edad pediátrica. La revisión incluye una revisión de los distintos sistemas de inhalación y los distintos fármacos inhalados, utilizados para el tratamiento del asma en la edad pediátrica. Esta revisión se actualizará anualmente, incluyendo información sobre fármacos, dispositivos, cámaras de inhalación, indicaciones y financiación. El Grupo REGAP espera que estas tablas sean una valiosa ayuda para los pediatras en su práctica clínica diaria y constituyen una eficaz herramienta de ET.